IDENTIFYING SOCIAL MEDIA RESOURCES AVAILABLE TO CAREGIVERS OF ALS PATIENTS. (8th November 2019) - Sanchez-Reilly, Sandra; Vutukuri, Sireesha; Reilly, Paula; Ross, Isabela S; Mejia, Andrea; Ross, Jeanette
Abstract: Background: Amyotrophic Lateral Sclerosis (ALS) is a progressive neurodegenerative disorder that causes muscle weakness, disability, and death, with survival of 3-5 years and affecting all populations including Hispanics. ALS patients are mostly cared for by family caregivers (FCG) who experience burden, psychological distress and impaired quality-of-life. Thus, FCG may not leave their homes to access resources. Social media might be a way to accessing support, but little is known about quality/quantity of AL- FCG resources. Research Objectives: To identify and categorize types of bilingual resources available to ALS-FCG in Facebook. Methods: We used Facebook both groups (public and closed groups) and pages and collected numbers-of-likes, organization type and resource provided. Bilingual search terms (Spanish) included ALS/ALS-caregiver. Results: 24 pages/31 groups in English vs. 37 pages/29 groups in Spanish. English resources had more likes/members (3510/790 vs.410/95; p<0.001) and were more active (60+ posts in recent month). Community resources and provision of social support were similarly shared through groups in both languages; advocacy was more prominent among Spanish groups (69%vs.39%, p<0.001). English pages significantly provided more social support (96% vs.65%, p<0.001), more caregiver skills (67%vs.49%, p<0.001), inspirational roles (88% vs.59%, p<0.001). Spanish pages and groups were better in providing news/research to FCG (59%vs.16%, p<0.001). Implications for research, policy or practice: Facebook provides numerous useful bilingual resources to ALS-FCG. FCG may receive social support, inspiration, training, news/research and advocacy. Further interventions need to actively improve the role of social-media in supporting bilingual ALS FCG and use it as a platform of dissemination.